Ukrainian food journal. Vol. 8. Issue 3 - National University of Food Technologies (My University, 2019)
Ukrainian Food Journal is an international scientific journal that publishes innovative papers of the experts in the fields of food science, engineering and technology, chemistry, economics and management. Ukrainian Food Journal – міжнародне наукове періодичне видання для публікації результатів досліджень фахівців у галузі харчової науки, техніки та технології, хімії, економіки і управління.
Keywords: chemistry; management; food science; machinery; economy; техніка; харчові науки; хімія; економіка; управління; экономика; управление; химия; техника